Understanding the complex interplay of victimization experiences, empathy and school climate in Tunisian schools - Chokri, Imed; Jarraya, Mohamed (Frontiers in Education, 2024)
Aim: Our study aims to examine the interactions between empathy, victimization, and the school climate in Tunisian primary schools. Method: In total, 312 school children (158 boys and 154 girls), with a mean age of 10.75 ± 1.32 years old participated voluntarily in the study. The students answered three scales that measure the School Climate, the Victimization, and the Empathy. Result: The results indicate a predominantly positive perception of the school climate by the students, both for the overall score (2.67 ± 0.64) and the scores of the different components of the school climate (ranging from 2.61 to 2.86). Also, girls seemed to have a more positive perception of the overall school climate, displaying higher scores (2.86 ± 0.54) compared to boys' scores (2.45 ± 0.67). Moreover, other results showed positive and statistically significant correlations (p < 0.01) between the different dimensions of the school climate. Conclusion: The findings highlight the importance of creating a safe and inclusive school environment where empathy is encouraged, and effective measures are in place to prevent and address victimization.